Paradigma Penerapan Putusan Nihil Berdasarkan Asas Kepastian Hukum, Keadilan dan Kemanfaatan - Rini Fathonah; Daffa Ladro Kusworo (Hang Tuah Law Journal, 2023)
The null verdict is a criminal sentence against someone who has received the criminal sentence with the maximum limit but must be retrialed due to certain cases so that the criminal sentence given is nil or the maximum limit has been reached. Zero verdicts are given to criminals who have received the maximum limit in the principal sentence. Criminal terms for a certain time may not exceed 20 years as stated in Article 12 paragraph (4) of the Criminal Code. Life imprisonment is stated in Article 67 of Criminal Code that if the perpetrator of a crime has been sentenced to life imprisonment, then additional punishment may not be given. The legal gap in the zero verdict is its application, which does not provide any punishment, which in this case has the potential to cause misunderstanding, so that its application needs to be straightened out by reviewing several court decisions, and reviewed from the principles of legal certainty, justice and benefit.. The research method used is normative juridical by studying, viewing, and examining several theoretical matters concerning the Criminal Code and conceptual as the new paradigm. The results of the study show that the Judge's Consideration in imposing Zero verdict, when associated with principles of certainty, practicality, and fairness, has reached all three parameters, even though it is more inclined to principle justice because the imposition of criminal sanctions in all decisions solely refers to criminal acts along with criminal threats by applicable regulations without being contrived.